ANALISIS DAMPAK PENGGUNAAN GADGET TERHADAP MINAT BACA SISWA SEKOLAH DASAR BERDASARKAN TINGKAT KEMAMPUAN AKADEMIK - Chindytia; Rini Kristiantari, Maria Goreti; Ana Tasya, Nengah Dwi Eriko; Senawa Dirgayusa, I Gede Astra; Winda Ariani, Ni Putu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology has increased gadget use among elementary school students, which may influence their reading interest. This study aimed to analyze the impact of gadget use on students’ reading interest based on academic ability levels. This research employed a qualitative approach with a case study design. The subjects consisted of homeroom teachers, Indonesian language teachers, and students categorized into high, medium, and low academic levels. Data were collected through interviews, observation, and questionnaires as supporting data. The data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The results show that most students use gadgets daily with relatively high duration, primarily for entertainment purposes. High-achieving students tend to have controlled gadget use and high reading interest. Meanwhile, medium-level students show high gadget use and low reading interest, while low-level students demonstrate varied reading interest despite high gadget use. These findings indicate that the impact of gadget use on reading interest is not absolute but depends on students’ usage patterns and self-control.